Working here or there? assessing the impact of job location on skill mismatch among young entry-level workers - Jamal, Muhammad Adib; Abd Rahman, Muhammad Daaniyall; Utit, Chakrin; Mokhyia, Nur Azreen (Universiti Malaysia Sabah Press, 2024)
The mismatch between the skills acquired by graduates from higher learning institutions and the areas of employment they enter is an important issue and should concern policymakers. This situation reflects inefficiency in the labor market, which can be caused by various factors. Among them may be the oversupply of graduates in a particular field in the labor market, or the expertise obtained not aligning with the needs of the industry. This situation can lead to the problem of skilled workers being underutilized in the labor market. As highly skilled human capital is a crucial input to both innovative activity and economic growth, their movements after graduation can potentially affect the dynamics of local development and, therefore, deserve thorough investigation. The main objective of this study is to determine the factors that influence skill mismatch with actual jobs offered among graduates from higher education institutions (HEIs) in Penang. This study adopted a survey approach with 185 university graduates from two public universities in Penang who graduated between the years 2019-2021. Descriptive analysis and logistic regression methods have been used to examine the relationship between salary, job location, and other variables such as family, friends, or hometown to the skill mismatch of these young workers. Results indicate that graduates from programs in Science, Mathematics, and Computer Sciences, and Engineering can find regular jobs that match their field of study. Interestingly, more than three-quarters of graduates from universities in Penang successfully get jobs under the Skilled Workers category. There are only 21% employed in the semi-skilled category and only 4% in the low-skilled category. Graduates working in the sector in the skilled worker’s category receive higher salaries compared to graduates working in semi-skilled and low-skilled categories.